“EL BONO DE DESARROLLO HUMANO Y SU IMPACTO EN EL BUEN VIVIR DE LOS BENEFICIARIOS DE LA PARROQUIA NUEVO PARAÍSO DEL CANTÓN NANGARITZA AÑO 2020” - Medina Lucero, María Priscila (2021)
The current thesis work is entitled “EL BONO DE DESARROLLO HUMANO Y SU IMPACTO EN EL BUEN VIVIR DE LOS BENEFICIARIOS DE LA PARROQUIA NUEVO PARAÍSO DEL CANTÓN NANGARITZA AÑO 2020”; it was developed according to the lineaments od Reglamento de Régimen Académico de la Universidad Nacional de Loja. This investigation held as general objective to determine the impact of Bono de Desarrollo Humano (BDH) among the beneficiaries from Nuevo Paraíso Parish, Nangaritza Canton in the year of 2020, in the achievement of good living understood from the quality of life; to do this it was precede in the following way: First, a theoretical reference review about the main inputs in the public political field was carried out highlighting the evaluation; and subsequently, the method to carry out the evaluation of the program was determined, which is the statistical test known as sign test. Likewise, the theoretical review about good living was addressed which allowed setting the variables to be investigated. Afterward, in order to apply the method, the technique of inquiry and interview was applied which brought out results. Finally, after analyzing the obtained results it was possible to establish the impact of Bono de Desarrollo Humano –BDH- on the beneficiaries' good living. In addition, it is outlined the positive impact in both, education and health; in a similar way in the work variable which refers to people's incomes. It is important to point out that two aspects were taken into account for this variable. Being the case, the first one was about the incomes, and the second one was about the economic activity (which resulted as a Z variable owing to the mining presence in the canton) where the deductive and descriptive methods were implemented. Finally, it was evidenced that the happiness variable is present in every beneficiary, therefore, it has a positive impact.